Defending Hermeneutics - Emily P Williams (University of Calgary, 2018)
This article offers several perspectives on the challenges of defending Gadamerian hermeneutics in applied research settings, specifically counselling psychology and nursing. Given the lack of methodological steps associated with the method, researchers employing hermeneutics can be vulnerable to scrutiny from others. We discuss the uncertainty that is inevitable when embarking on hermeneutic inquiry and provide personal accounts of how we have encountered the uncertain nature of hermeneutics.